2015
DOI: 10.18410/jebmh/2015/535
|View full text |Cite
|
Sign up to set email alerts
|

A S Tudy on Concomitant Occurrence of Subclinical Hypothyroidism and Reduced Growth Hormone Secretion on Fibromyalgia

Abstract: Fibromyalgia, the abnormal pain perception by an individual has a complex etiopathogenesis with multifactorial involvement. The current study was conducted in 39 clinically diagnosed cases of fibromyalgia in NEIGRIHMS shilling from September 2013 to March 2014. Data from the cases when compared with 25 numbers of age matched control revealed a nonsignificance of growth hormone in fibromyalgia with p value >0.05. The study also showed a significant difference in TSH concentration among cases and control as indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Our results are in partial agreement with a recent study [40] which found no significant difference in the TSH concentration among 82% of FMS patients while only 18% FMS patients were found with elevated level of TSH which was probably due to the misdiagnosis of subclinical hypothyroidism as FM [40]. It has been found that the levels of thyroid hormones are usually in normal range even if the patients show some symptoms of hypothyroidism [41].…”
Section: Tsh Level In Fmssupporting
confidence: 91%
“…Our results are in partial agreement with a recent study [40] which found no significant difference in the TSH concentration among 82% of FMS patients while only 18% FMS patients were found with elevated level of TSH which was probably due to the misdiagnosis of subclinical hypothyroidism as FM [40]. It has been found that the levels of thyroid hormones are usually in normal range even if the patients show some symptoms of hypothyroidism [41].…”
Section: Tsh Level In Fmssupporting
confidence: 91%
“…BAT can be located deep within the neck and trunk, near the great vessels, in the supraclavicular, supra-axial, paraspinal, and perirenal regions, in sympathetic ganglia and striations of the skeletal muscles and, finally, just below the skin 7 , 15 , 18 . Resting BAT activity and FM incidence are higher in women 15 , 19 21 , with lower adaptive thermogenesis in this group 7 .…”
Section: Introductionmentioning
confidence: 79%